2023
DOI: 10.2196/38371
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Comprehensive Health and Stringency Indexes in Evaluating Government Responses for Containing the Spread of COVID-19 in India: Ecological Time-Series Study

Abstract: Background Many nations swiftly designed and executed government policies to contain the rapid rise in COVID-19 cases. Government actions can be broadly segmented as movement and mass gathering restrictions (such as travel restrictions and lockdown), public awareness (such as face covering and hand washing), emergency health care investment, and social welfare provisions (such as poor welfare schemes to distribute food and shelter). The Blavatnik School of Government, University of Oxford, tracked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…That was studied by Ftiti et al (2021), who empirically confirmed that the lockdown announcement in China had a significantly negative effect on the financial markets. We extend those findings by identifying the relationship between the US, Europe, and Japan and using the Stringency Index as the index has yet been used mainly in healthrelated studies (e.g., Dzator et al, 2021;Kishore et al, 2023).…”
Section: Discussionmentioning
confidence: 61%
“…That was studied by Ftiti et al (2021), who empirically confirmed that the lockdown announcement in China had a significantly negative effect on the financial markets. We extend those findings by identifying the relationship between the US, Europe, and Japan and using the Stringency Index as the index has yet been used mainly in healthrelated studies (e.g., Dzator et al, 2021;Kishore et al, 2023).…”
Section: Discussionmentioning
confidence: 61%
“…Implementation and feasibility of strict societal restrictions differ for high-income and low-income countries. For instance, in a country like India, strict government policies may not lead to better compliance but can overwhelm the healthcare systems [ 31 ].…”
Section: Discussionmentioning
confidence: 99%